Efek Macam dan Dosis Pupuk Kalium Terhadap Pertumbuhan Tanaman Jagung Manis (Zea mays. L) Varietas Paragon - fenia aknantasari (AGRONISMA, 2022)
Sweet corn (Zea mays Saccharata Sturt) is a food crop that ranks third after wheat and rice. National corn production is still unable to meet market demand. One of the efforts that can be done to increase sweet corn production is fertilization. Fertilizers containing macro nutrients N, P, and K are needed by sweet corn plants. The element K is the second macro nutrient after N which is most widely absorbed by plants. Elemental K in plants is in the form of K+ cations. Loss of K is very high due to leaching from the soil surface (Utomo et al., 2016). The purpose of this study was to determine the effect of potassium fertilizer and its application dose on the growth of sweet corn varieties of paragon. This study used a split plot design consisting of main plots of potassium fertilizer (KCl and KNO3) and subplots, namely the application dose (50 kg/ha, 100 kg/ha, 150 kg/ha, and 200 kg/ha) as well as control. The results showed that there was an interaction between types of potassium fertilizer and application dose of potassium fertilizer on plant height, number of leaves, leaf area and chlorophyll content.Keyword : potassium fertilizer, sweet corn, KCl, KNO3, paragon varieties